2013
DOI: 10.1186/1471-2407-13-445
|View full text |Cite
|
Sign up to set email alerts
|

High-risk human papillomavirus (HPV) DNA sequences in metaplastic breast carcinomas of Mexican women

Abstract: BackgroundMetaplastic carcinoma, an uncommon subtype of breast cancer, is part of the spectrum of basal-like, triple receptor-negative breast carcinomas. The present study examined 20 surgical specimens of metaplastic breast carcinomas, for the presence of high-risk Human papillomavirus (HPV), which is suspected to be a potential carcinogenic agent for breast carcinoma.MethodsMastectomy specimens from patients harboring metaplastic breast carcinoma, as defined by the World Health Organization (WHO), and who at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
27
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 44 publications
6
27
2
4
Order By: Relevance
“…In Latin America, the rate is a little lower. It is reporting between 5–40% of positivity [ 26 , 27 , 28 , 34 ], particularly in the case of Herrera et al (2013) [ 34 ], who report a 40% of positivity. Their samples were from metaplastic breast tumours, a subset of breast tumours, characterised for being more aggressive and worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Latin America, the rate is a little lower. It is reporting between 5–40% of positivity [ 26 , 27 , 28 , 34 ], particularly in the case of Herrera et al (2013) [ 34 ], who report a 40% of positivity. Their samples were from metaplastic breast tumours, a subset of breast tumours, characterised for being more aggressive and worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that several authors have suggested that the presence of HPV is associated with smaller breast tumours [ 24 , 27 , 32 , 34 ], when compared with negative tumours for viral infection. In this work, despite the fact that we found no statistical significant relationship, HPV-positive breast tumours were found mainly among the groups T1 and T2 lesions with a maximum size of 50 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only those in a subset develop cervical cancer. Recently, HPVs have been implicated in the development of head and neck, lung, and breast cancers (8)(9)(10).…”
mentioning
confidence: 99%
“…A study from Singapore showed a high prevalence of infection with high-risk HPV in breast cancer patients [45]. A Mexican study detected high-risk HPV DNA in 8 (40.0%) of 20 metaplastic breast carcinomas [7 (87.5%) with HPV-16 infection and 1 (12.5%) with HPV-18 infection)] [46]. Another study from China, using paraffin-embedded breast cancer tissue samples, detected HPV18 E6 and HPV18 E7 in approximately 30% of the samples [47].…”
Section: Triple-negative Breast Carcinoma In East Asiansmentioning
confidence: 99%